Repairing invasive cervical root resorption by glass ionomer cement combined with mineral trioxide aggregate - Ya-Ching Chang; Hsueh-Jen Lin; Yuan-Ling Lee; Li-Chuan Liu; Jiiang-Huei Jeng (Elsevier, 2012)
Cervical invasive root resorption is a type of external inflammatory root resorption that is relatively uncommon and aggressive, and leads to loss of tooth structure. A diagnosis of cervical invasive root resorption depends on careful routine clinical and radiographic examinations. This report describes the diagnosis and successful treatment of a 41-year-old male patient with invasive cervical root resorption at tooth #21. The distinctive feature was a large resorptive defect at the cervicopalatal aspect of the maxillary central incisor involving the root-canal space. A radiographic examination revealed a large periradicular lesion and severe periodontal damage around this tooth. The defect was surgically repaired using resin-reinforced glass ionomer cement (GIC) and mineral trioxide aggregate (MTA) to restore the coronal half and apical half of the resorption cavity, respectively. Thereafter, conventional root-canal treatment was performed. The 11-month recall revealed good healing of both the periodontal and periradicular conditions and no obvious clinical symptoms. This case provides a new treatment modality to repair defects of cervical invasive root resorption and promote the healing of periodontal defects.